2016
DOI: 10.1177/1545968315624780
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Paretic and Nonparetic Limb Peak Propulsive Forces to Changes in Walking Speed in Individuals Poststroke

Abstract: Background Recent rehabilitation efforts after stroke often focus on increasing walking speed because it is associated with quality of life. For individuals poststroke, propulsive force generated from the paretic limb has been shown to be correlated to walking speed. However, little is known about the relative contribution of the paretic versus the non-paretic propulsive forces to changes in walking speed. Objective The primary purpose of this study was to determine the contribution of propulsive force gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 31 publications
2
78
0
2
Order By: Relevance
“…Consistent with previous cross-sectional studies, our results showed all measurements of propulsion were correlated with walking speed (Bowden et al, 2006; Campanini and Merlo, 2009; Hsiao et al, 2015). In addition, the relationships between peak propulsive force and mean propulsive value versus walking speed were stronger compared to propulsive impulse (Figure 2 A-C).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous cross-sectional studies, our results showed all measurements of propulsion were correlated with walking speed (Bowden et al, 2006; Campanini and Merlo, 2009; Hsiao et al, 2015). In addition, the relationships between peak propulsive force and mean propulsive value versus walking speed were stronger compared to propulsive impulse (Figure 2 A-C).…”
Section: Discussionsupporting
confidence: 92%
“…Because asymmetry in propulsion was commonly observed in individuals poststroke (Bowden et al, 2006), propulsion from the non-paretic limb could also influence walking speed (Hsiao et al, 2015). Our results demonstrated that accounting for both limbs' peak propulsive forces and cadence further enhanced the ability of measurement of propulsion to reflect changes in walking speed (Figure 4B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GRFs were used to compute PP and non-PP and this study's primary kinetic outcome: interlimb propulsion symmetry. PP was defined as the anterior GRF measured during the paretic limb's stance phase, normalized by body weight (% bw) (65,79,86,(89)(90)(91).…”
Section: Clinical Evaluationsmentioning
confidence: 99%
“…However, this characteristic pattern of joint-level coordination in elderly gait, associated with reduced F P and thought to precede the slowing of preferred speed, is fundamentally different from that associated with walking slower. A more complete understanding of the biomechanical changes that precede the slowing of walking speed may have broad implications; similar and simultaneous interdependent changes in walking speed, F P , and joint kinetics also emerge with more acute mobility impairment such as that following stroke (Farris et al, 2015; Hsiao et al, 2015a). However, unlike the well-documented biomechanical changes due to walking speed, to our knowledge no study to date has successfully decoupled the independent effects of reducing F P on joint power generation from the neuromuscular constraints that may precipitate them.…”
Section: Introductionmentioning
confidence: 99%